2011
DOI: 10.1016/j.ejcts.2010.11.018
|View full text |Cite
|
Sign up to set email alerts
|

The SOURCE Registry: what is the learning curve in trans-apical aortic valve implantation?

Abstract: Although the incidence of technical intra procedural complications has trended downward, reflecting the learning curve for TA-AVI, 30-day mortality was unchanged, likely due to patient co-morbidities not captured by preoperative risk variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 20 publications
2
33
0
2
Order By: Relevance
“…Ein Unterschied zwischen den beiden Zugangswegen scheint hinsichtlich der 30TageMortalität nicht zu bestehen, wie Bleiziffer [17] an 203 Hochrisikopatienten mit einer Mortalitätsrate von 10,8 % (transfemoral) und 8,3 % (transapikal) zeigen konnte. Die intraoperative Komplikationsrate konnte mit zunehmender Erfahrung der implantierenden Zentren reduziert werden, so dass die Frühmortalität gegenwärtig maßgeblich von der Komorbidität der Patienten bestimmt wird, wie Wendler [18] in einer kürzlich veröffentlichten Studie berichtet. Die 1Jah-resÜberlebenswahrscheinlichkeit nach transapikaler TAVI wird in der Literatur mit 70-85 % [18,19] angegeben.…”
Section: Risiken Und Grenzen Des Katheterbasierten Aortenklappenersatzesunclassified
“…Ein Unterschied zwischen den beiden Zugangswegen scheint hinsichtlich der 30TageMortalität nicht zu bestehen, wie Bleiziffer [17] an 203 Hochrisikopatienten mit einer Mortalitätsrate von 10,8 % (transfemoral) und 8,3 % (transapikal) zeigen konnte. Die intraoperative Komplikationsrate konnte mit zunehmender Erfahrung der implantierenden Zentren reduziert werden, so dass die Frühmortalität gegenwärtig maßgeblich von der Komorbidität der Patienten bestimmt wird, wie Wendler [18] in einer kürzlich veröffentlichten Studie berichtet. Die 1Jah-resÜberlebenswahrscheinlichkeit nach transapikaler TAVI wird in der Literatur mit 70-85 % [18,19] angegeben.…”
Section: Risiken Und Grenzen Des Katheterbasierten Aortenklappenersatzesunclassified
“…18 Because of the improved knowledge of patient screening, assessment of the access vessels and annulus, prosthesis selection, procedural planning, and safety networks (eg, crossover wires) to avoid the deleterious outcome after vascular insults, complications are prevented or treated at an early stage of occurrence, which has made TAVR much safer in 2014 compared with 2006. 37,48,51 all-cause mortality was 0% and 3.5%, the rate of cerebrovascular events was 0% versus 4.5%, and the rate of major strokes was 0% versus 3.5% in the low-and intermediate-risk group, respectively. There were no differences between the 2 groups with regard to major or life-threatening bleeding, the occurrence of acute renal failure, and major or minor access site complications.…”
Section: Tavr In Younger Lower-risk Patientsmentioning
confidence: 99%
“…Hence, data from Edwards transcatheter valve registries, [34][35][36][37][38] Medtronic Core valve registries, [39][40][41][42][43] and mixed multicenter and national registries [44][45][46][47][48][49][50][51] containing a broad range of patients treated transfemorally, transapically, or with a direct aortic, subclavian, and carotid approach are the only resources potentially supporting an expansion of indications. The predominant valves evaluated in these registries were the balloon-expandable Edwards SAPIEn, the Edwards SAPIEn XT, and the self-expandable Medtronic CoreValve prosthesis.…”
Section: Moving Toward Lower-risk Patients: Circumstantial Evidence Fmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3) The most recent clinical studies showed that the rate of death from any cause at 1 year among patients treated with TAVI was 25%-30%. Wendler et al 4) described the early results from the multicenter SOURCE registry of European countries for Sapien valve implantation. He reported a 92.7% success rate with 2.1% reoperation, 7.3% pacemaker implantation, 7.1% dialysis, and 2.6% major vascular complications.…”
Section: Present Situation Of Tavi Worldwidementioning
confidence: 99%